Large-scale EEG neural network changes in response to therapeutic TMS - Gold, Michael C.; Yuan, Shiwen; Tirrell, Eric; Kronenberg, E. Frances; Kang, Jee Won D.; Hindley, Lauren; Sherif, Mohamed; Brown, Joshua C.; Carpenter, Linda L. (Brain stimulation, 2022)
Transcranial magnetic stimulation (TMS) is an effective therapy for patients with treatment-resistant depression. TMS likely induces functional connectivity changes in aberrant circuits implicated in depression. Electroencephalography (EEG) “microstates” are topographies hypothesized to represent large-scale resting networks. Canonical microstates have recently been proposed as markers for major depressive disorder (MDD), but it is not known if or how they change following TMS. Resting EEG was obtained from 49 MDD patients at baseline and following six weeks of daily TMS. Polarity-insensitive modified k-means clustering was used to segment EEGs into constituent microstates. Microstates were localized via sLORETA. Repeated-measures mixed models tested for within-subject differences over time and t-tests compared microstate features between TMS responder and non-responder groups. Six microstates (MS-1 - MS-6) were identified from all available EEG data. Clinical response to TMS was associated with increases in features of MS-2, along with decreased metrics of MS-3. Nonresponders showed no significant changes in any microstate. Change in occurrence and coverage of both MS-2 (increased) and MS-3 (decreased) correlated with symptom change magnitude over the course of TMS treatment. We identified EEG microstates associated with clinical improvement following a course of TMS therapy. Results suggest selective modulation of resting networks observable by EEG, which is inexpensive and easily acquired in the clinic setting. •EEG microstates are believed to represent transient activations of global networks.•Distinct microstate networks changed in clinical response to TMS.•These changes may reflect default-mode network recalibration in antidepressant response.